THE EFFECT OF WARM COMPRESS ON BACK PAIN IN THE THIRD TRIMESTER PREGNANT WOMEN IN OUR CLINIC WITH SAND SPIRITUAL PANGARAAN - Ernamari; Pinem Srinila Br; Pasaribu Uli Yuslina (International Journal of Midwifery Research, 2022)
Back pain in Indonesia is more common in pregnant women and in the 40 year old age group. Overall, back pain is the most common complaint with a prevalence rate of 49%. However, around 80-90% of those who experience back pain state that they have not made any effort to overcome the onset of these symptoms, in other words, only about 10-20% of those who seek medical treatment go to health workersThis study used Quasy Experimental Design research, with 1 group pretest post test design. With the aim of knowing the effectiveness of warm compresses for pregnant women Tm 3 who experience back pain at the Kita Bersama Pasir Pangaraian Rohul Clinic. Year 2021.The population and samples in this study were all third trimester pregnant women at the Kita Bersama Pasir Pangaraian Rohul Clinic. In 2021. With a total of 20 pregnant women.After conducting research at the Kita Bersama Pasir Pangaraian Rohul Clinic. In 2021. The statistical test results obtained a p value of 0.000, so it can be concluded that there is a significant difference between pain intensity before and after being given warm compresses. So that warm compresses performed on third trimester pregnant women have an effect on reducing the intensity of back pain felt by the mother.